False data injection in power smart grid and identification of the most vulnerable bus; a case study 14 IEEE bus network - Xiang Zhong (Elsevier, 2021)
Smart grids are one of the most important structures based on cyber–physical devices. Therefore, these grids should be more reliable and efficient when increasing consumption. In recent years, however, with the automation of power grids and data transferring in a telecommunications infrastructure, the possibility of planning cyber-attacks has become a significant threat to systems integrity. Well-planned cyber-attacks can have catastrophic effects on the system to the extent that they may lead to a global blackout. It has been proven that, the optimization of the budgets for attack and defense in a power grid through cyber-attack is so essential. The aim of the present paper is investigate and simulate the most vulnerable operating bus using the state estimation technique through a new algorithm. The false data injection is performed on the data sent from the Phasor Measurement Units in such a way that it is not detectable to the grid dispatching operator under the invasion. In other words, when a cyber-attack occurs, the defender does not notice the attack and thus the estimated modes are destroyed. The proposed algorithm is implemented on a 14 IEEE bus network, and the best bus in terms of exposure under attack is identified. The proposed algorithm is based on the results obtained from state estimating of the grid after occur a cyber-attack on different buses. It was found that, the best bus to carry the attack was bus number 5, which causes the most changes in state variables with the least measurement damage. In addition, the most damage to the grid occurs when a cyber-attack causes the most damage in estimating the state of the most grid state variables.